Fetal Head Station at Second-Stage Dystocia and Subsequent Trial of Labor After Cesarean Delivery Success Rate. Issue 1 (January 2021) - Rottenstreich, Amihai; Meyer, Raanan; Rottenstreich, Misgav; Elami, Matan; Lewkowicz, Aya; Yagel, Simcha; Tsur, Abraham; Rosenbloom, Joshua I.; Yagel, Itay; Yinon, Yoav; Levin, Gabriel
Abstract : OBJECTIVE: To investigate whether fetal head station at the index cesarean delivery is associated with a subsequent trial of labor success rate among primiparous women. METHODS: A retrospective cohort study conducted at two tertiary medical centers included all primiparous women with subsequent delivery after cesarean delivery for second-stage dystocia during 2009–2019, identified from the electronic medical record databases. Univariate and multivariate analyses were performed to assess the factors associated with successful trial of labor after cesarean (TOLAC) (primary outcome). Additionally, all women with failed TOLAC were matched one-to-one to women with successful TOLAC, according to factors identified in the univariate analysis. RESULTS: Of 481 primiparous women with prior cesarean delivery for second-stage dystocia, 64.4% (n=310) attempted TOLAC, and 222 (71.6%) successfully delivered vaginally. The rate of successful TOLAC was significantly higher in those with fetal head station below the ischial spines at the index cesarean delivery, as compared with those with higher head station (79.0% vs 60.5%, odds ratio [OR] 2.46, 95% CI 1.49–4.08). The proportion of neonates weighing more than 3, 500 g in the subsequent delivery was lower in those with successful TOLAC compared with failed TOLAC (29.7% vs 43.2%, OR 0.56, 95% CI 0.33–0.93). In a multivariable analysis, lower fetal head station at the index cesarean delivery was the only independent factor associated with TOLAC success (adjusted OR 2.38, 95% CI 1.43–3.96). Matching all women with failed TOLAC one-to-one to women with successful TOLAC, according to birth weight and second-stage duration at the subsequent delivery, lower fetal head station at the index cesarean delivery remained the only factor associated with successful TOLAC. CONCLUSION: Lower fetal head station at the index cesarean delivery for second-stage dystocia was independently associated with a higher vaginal birth after cesarean rate, with an overall acceptable success rate. These findings should improve patient counseling and reassure those who wish to deliver vaginally after prior second-stage arrest. Abstract : Lower fetal head station at prior cesarean delivery for second-stage dystocia is associated with higher rate of vaginal birth after cesarean delivery.